CRIMINAL LIABILITY IN THE CRIME OF CORRUPTION IN LAND ACQUISITION FOR THE CONSTRUCTION - Mulyanto, Akh; Farhana, Farhana (Awang Long Law Review, 2025)
Land acquisition procedures carried out in the context of the construction of the Tapin Dam are qualified as part of land acquisition for the public interest, as referred to in laws and regulations. This qualification is in line with the provisions of 65 of 2006 concerning to Presidential Regulation.36i of 2005, which states that infrastructure development for the benefit of water resources, including dams, is a form of development for the public interest. In this context, the Kalimantan II River Regional Center held land acquisition activities for the construction of the Tapin Dam through the formation of a land acquisition committee as stipulated in the Presidential Regulation. Proof in the Crime of Corruption of land acquisition for the Construction of the Tapin Dam is by proving criminal acts (elements of the article charged), the ability to be responsible, mistakes in the form of intentionality or forgetfulness and the absence of a reason for criminal removal. As for the criminal liability, that the defendant had received land change money from the community that the defendant used for the benefit of his family, so that the defendant was punished criminally and fined. The judge's consideration in Decision No. 10/PID. SUS-TPK/2023/PT BJM regarding the crime of corruption in land acquisition for the construction of the Tapin Dam stated that the defendant was proven to have committed an unlawful act as stipulated in Article 12 letter e of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, which has been amended and supplemented by Law Number 20 of 2001, so that the verdict is considered appropriate. the defendant had made an agreement with the witness Sogianor Bin Ilar (deceased) as the Head of Pipitak Jaya Village and a member of the Land Acquisition Team in the Implementation of Land Acquisition for the Construction of the Tapin Dam as a state administrator, and the defendant as a participant in the investigation, so that the crime occurred.